In vitro and in vivo antibacterial activities of CS-807, a new oral cephalosporin. - Utsui, Y (1987)
CS-807 is a new oral prodrug of R-3746, a cephalosporin derivative, with potent in vitro and in vivo antibacterial activity against both gram-positive and gram-negative bacteria. The susceptibility of about 1,200 clinical isolates to R-3746 was determined by the agar dilution method. Ninety percent or more of pathogens such as Staphylococcus aureus, streptococci, Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, indole-positive and indole-negative Proteus spp., Providencia rettgeri, and Haemophilus influenzae were inhibited at concentrations ranging less than or equal to 0.01 to 1.56 micrograms/ml. Furthermore, at a concentration of 3.13 micrograms/ml, 50% or more of Staphylococcus epidermidis, Morganella morganii, Citrobacter freundii, and Serratia marcescens strains were also inhibited. Pseudomonas aeruginosa and Xanthomonas maltophilia were resistant to R-3746. The activity of R-3746 was scarcely influenced by several growth conditions. R-3746 was highly resistant to hydrolysis by beta-lactamases derived from various species of bacteria. Killing-curve studies demonstrated bactericidal activity of R-3746 at concentrations above the MIC. R-3746 showed high affinity for penicillin-binding proteins 1, 3, and 4 of Staphylococcus aureus and 1A, 1Bs, and 3 of Escherichia coli. Systemic infections in mice caused by various pathogens, including beta-lactamase-producing strains, responded well to therapy with oral doses of CS-807.